"Just let us be" discrimination against LGBT students in the Philippines - Thoreson, Ryan Richard 1984-; Human Rights Watch (Organization) ([New York, N.Y.] Human Rights Watch, 2017)
"This report documents the range of abuses against lesbian, gay, bisexual, and transgender (LGBT) students in secondary school. It details widespread bullying and harassment, discriminatory policies and practices, and an absence of supportive resources that undermine the right to education under international law and put LGBT youth at risk"--Publisher's description.
Summary -- Key Recommendations To the Congress of the Philippines -- To the Department of Education -- To Local Officials -- To School Administrators -- Methodology -- Glossary -- I. Background Existing Protections for LGBT Youth and Their Limitations Child Protection Policy -- The Anti-Bullying Law -- Comprehensive Sexuality Education -- Effects of Bullying and Discrimination -- II. Bullying and Harassment Physical Bullying -- Sexual Assault and Harassment -- Verbal Harassment -- Cyberbullying -- Intervention and Reporting -- III. Creating a Hostile Environment School Enforcement of Stereotyped Gender Norms Uniforms and Hair Length Restrictions -- Access to Facilities -- Gender Classifications -- Hostility Toward Same-Sex Relationships -- Pressure to Conform to Stereotypes -- IV. Exclusion from Curricula and Resources School Curricula -- Comprehensive Sexuality Education -- Counseling and Support -- Student Organizations -- V. Philippines' Legal Obligations to Protect LGBT Students Right to Education -- Violence and Bullying -- Right to Health -- Freedom of Expression -- Freedom from Discrimination -- Recommendations To the President of the Philippines -- To the Congress of the Philippines -- To the Department of Education -- To Local Officials -- To School Administrators -- Acknowledgments.
"June 21, 2017"--Table of contents page.
"Ryan Thoreson, a researcher in the LGBT Rights Program, wrote this report"--Acknowledgments.
Includes bibliographical references.
Also available on the Human Rights Watch website.
UCWS-3219g donated by Ryan Thoreson - September 2017
Keywords: Lesbian students -- Abuse of -- Philippines; Gay students -- Abuse of -- Philippines; Bisexual students -- Abuse of -- Philippines; Sexual minorities -- Abuse of -- Philippines; Gay rights -- Philippines; Gender identity -- Social aspects -- Philippines; Sexual minorities -- Education -- Philippines; Sexual minorities -- Violence against -- Philippines; Homosexuality and education -- Government policy -- Philippines; Philippines -- Social conditions -- 21st century